Perception of Organizational Justice Towards Organizational Commitment Among Employees of PT. Jayadi Samudera Lines Through Job Satisfaction Mediation - Dhani Husada Waluyajati; Idha Rahayuningsih (Journal Research of Social Science, Economics, and Management, 2025)
The purpose of this study was, to determine the effect of perceptions of organizational justice on organizational commitment in employees of PT. Jayadi Samudera Lines with mediation of job satisfaction. The population of this study is using Nonprobability Sampling. The research method used is quantitative. Research data were collected by distributing questionnaires directly consisting of a scale of perceptions of organizational justice, job satisfaction, and organizational commitment. The scale in this study uses a Likert scale with 6 answer choices and 5 answer choices. The research measuring instrument used was the perception of organizational justice which was made by the researcher based on Moorman's theory (1991), the job satisfaction scale made by the researcher based on Spector's theory (1994) translated by Junaedi et al (2021) and the organizational commitment scale made by Allen & Meyer (1990) and revised by Stephen Jaros (2007). The validity test uses content validity and the reliability test uses Cronbach's Alpha. Data analysis techniques use regression and mediation analysis tests. The results showed that perceptions of organizational justice can have a direct effect on organizational commitment with a p-value of 0.002 and an Estimate value of 0.318. And can affect through the mediation of job satisfaction with a p-value of 0.001 and an Estimate value of 0.391. Thus it can be concluded that job satisfaction can be a mediating role.